Survey of Canadian certified coaches` understanding and application of learning theory in horse training - Wentworth-Stanley, C.; Randle, H.; Wolframm, I. (DCA Report; Nr. 044, 2014)
The use of learning theory (LT) in the training of horses has received much attention recently. Its incorrect application has been shown to increase equine behavioural problems resulting in an increased risk of injury to horse and rider and a decrease in equine welfare. This study was a constructive replication of Warren-Smith and McGreevy`s 2008 Australian (A) study and used a questionnaire to determine Canadian (C) coaches` understanding and application of LT. The demographic section was adapted to reflect differences in the Canadian coaching system. Using closed questions, coaches were asked to rate the usefulness of positive reinforcement (PR), negative reinforcement (NR) as well as punishment (P). Open-ended questions allowed the coaches to explain their use of each and their answers were marked according to Skinner`s 1953 definitions. Further closed questions were added to explore the frequency at which coaches` horses experienced behaviour problems and to allow the rating of the effectiveness of 6 different rewards. Comparisons were made between the C and A coaches` responses. With a sample size of 1879, the response rate of 20.8% showed a good representation of C coaches. Significantly fewer C (12.2%) than A (19.3%) coaches rated NR as very useful (P<0.001). The majority of C and A coaches explained NR as P, which may explain the positive relationship between the increase in the frequency of behaviour problems and the usefulness of NR (W=51993.0, P<0.005). The majority of A (79.5%) and C (81.2%) coaches rated PR as very helpful although 72.9% of C coaches explained it either incorrectly or as NR or NR and PR. Significantly more A (5.2%) than C (2.6%) coaches deemed P very useful (P<0.05) and explained it correctly (46.3% and 33.9%, respectively: P<0.001). Of the C coaches experiencing behaviour problems 5-10 times/week, 43.3% rated punishment as useful. As in the A study, the majority of coaches (82.3%) considered releasing the aid the most effective reward. In essence this is NR. Despite C coaches rating PR more useful than NR, they are primarily using NR. This study confirmed the findings of the A study. Canadian certified coaches do not seem to have a sound understanding of the use, application and terminology of LT. LP: As LT governs the way animals learn, coaches, whose supposed expertise is in the realm of training horses, should thoroughly understand and apply its principles effectively. Confusion as to its use and application exists in Canada, as in Australia. The comprehensive inclusion of LT in coaching manuals would improve equine welfare, and reduce the injuries to horse and rider often attributed to equine behaviour problems.